A NEW SECURE BLOCK-CHAIN FOR ADMISSION PROCESSING IN EDUCATIONAL INSTITUTIONS (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
Blockchain technology with its secure mechanism of maintaining data and transactions in shared, immutable, distributed ledgers has become very relevant today and is increasingly used for financial applications. This paper proposes the use of consortium blockchain and smart contracts for secure, transparent and automated processing of student applications received by educational institutions. The students applying for admissions in educational institutions need